Analysis of Ki-67 expression as clinicopathological parameters in predicting the prognosis of adenoid cystic carcinoma - Silvi Kintawati; Murnisari Darjan; Winny Yohana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Adenoid cystic carcinoma is a malignant salivary gland tumor located in the head and neck region. Although complete surgical resection and complementary radiotherapy have been shown to improve long-term survival rates, the prognosis of adenoid cystic carcinoma remains poor. Ki-67 expression is considered a marker for the cellular proliferation rate, the detection of its expression usually being related to the aggressiveness and unfavorable prognosis of adenoid cystic carcinoma in the salivary gland. Purpose: This study was conducted to quantify the expression of Ki-67 in adenoid cystic carcinoma and to correlate the result with clinical parameters and histopathological grading in determining the prognosis. Methods: Twenty three cases of salivary gland adenoid cystic carcinoma were identified at the Department of Anatomical Pathology, Dr. Hasan Sadikin Hospital between 2013 and 2015. Clinical data such as age, gender, location of tumor and histopathological grading was also collected. The expression of Ki-67 was assessed by immunohistochemical means to determine the correlation of Ki-67 with clinical parameters and histopathological grading. Results: There were no significant differences between the expression of Ki-67 and clinical parameters, although a very strong correlation existed between the expression of Ki-67 and histopathological grading (p < 0.01). Conclusion: There were no correlation between the expression of Ki-67 and clinical parameters, although a correlation existed between the expression of Ki-67 and histopatological grading in salivary gland adenoid cystic carcinoma. Thus, clinical parameters were unusable in determining the prognosis of adenoid cystic carcinoma, although Ki-67 expression could be used for this purpose.